2020
DOI: 10.5653/cerm.2020.00423
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide, 8-hydroxydeoxyguanosine, and total antioxidant capacity in human seminal plasma of infertile men and their relationship with sperm parameters

Abstract: Objective: Oxidative stress plays a key role in the pathogenesis of male infertility. But, the adverse effects of oxidative biomarkers on sperm quality remain unclear. This study aimed to investigate the levels of nitric oxide (NO), 8-hydroxydesoxyguanosine (8-OHdG), and total antioxidant capacity (TAC) oxidative biomarkers in seminal plasma and their relationship with sperm parameters.Methods: A total of 77 volunteers participated in the study, including fertile (n=40) and infertile men (n=37). NO, 8-OHdG, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Infection only with CT may generate fewer RONS, which also induces less LPO probably because antioxidant systems are still active, increasing TAC levels. However, these levels are similar to those found in other infertile populations [ 27 ] but without seminal HPV, CT, or coinfection, then other factors such as lifestyle choices (tobacco and alcohol consumption) and environmental factors trigger testicular sources of RONS [ 11 , 26 ], which could stimulate OS in CT infection. Moreover, seminal TAC levels were significantly lower in HPV infection or CT coinfection, resembling other infertile male populations [ 27 ], which may decrease the percentage of motile A and non-progressive motility (% motile A + B).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Infection only with CT may generate fewer RONS, which also induces less LPO probably because antioxidant systems are still active, increasing TAC levels. However, these levels are similar to those found in other infertile populations [ 27 ] but without seminal HPV, CT, or coinfection, then other factors such as lifestyle choices (tobacco and alcohol consumption) and environmental factors trigger testicular sources of RONS [ 11 , 26 ], which could stimulate OS in CT infection. Moreover, seminal TAC levels were significantly lower in HPV infection or CT coinfection, resembling other infertile male populations [ 27 ], which may decrease the percentage of motile A and non-progressive motility (% motile A + B).…”
Section: Discussionsupporting
confidence: 81%
“…However, these levels are similar to those found in other infertile populations [ 27 ] but without seminal HPV, CT, or coinfection, then other factors such as lifestyle choices (tobacco and alcohol consumption) and environmental factors trigger testicular sources of RONS [ 11 , 26 ], which could stimulate OS in CT infection. Moreover, seminal TAC levels were significantly lower in HPV infection or CT coinfection, resembling other infertile male populations [ 27 ], which may decrease the percentage of motile A and non-progressive motility (% motile A + B). Gholinezhad et al found a lower percentage of motility in infertile men compared to fertile men, although with typical values of this sperm parameter according to the WHO [ 27 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…For example, arginine, an amino acid present in hazelnut, is required for normal spermatogenesis; a precursor for polyamines found in the male reproductive system, especially the epididymis and affects cell growth, differentiation, and sperm motility. It is also a precursor of antioxidant nitric oxide (NO) that regulates spermatogenesis, sperm hyperactivation, sperm motility, maturation, acrosome reaction, capacitation, and sperm fertilization (Gholinezhad et al., 2020; Özer Kaya et al., 2020). On the other hand, a main mineral in hazelnut, potassium, is needed to maintain sperm osmotic pressure, volume, and motility (Vílchez et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with asthenozoospermia show enhanced mtDNA copy number and reduced mtDNA integrity that are associated with higher ROS generation (Bonanno et al, 2016). Accordingly, other reports underlined the significant association between NO and 8-OHdG levels and semen parameters abnormalities (Gholinezhad et al, 2020), supporting redox status assessment for helping male infertility diagnosis and monitoring.…”
Section: The Pathological Role Of Ros In Spermatozoamentioning
confidence: 95%